Penggunaan E-Banking Terhadap Transaksi Nasabah Pada PT. Bank Syariah Indonesia KCP Blangpidie Kuta Tuha - Sella Puspita; Wardah Muharriyanti Siregar (Jurnal Indonesia Sosial Teknologi, 2022)
E-Banking is an online service from banking that is operated using internet technology which is accessed through browsers, crome and others, with the aim of making it easier for customers to make transactions. Total use of e-banking at Pt. Bank Syariah Indonesia Kcp Blangpidie Kuta Tuha in 2020 is 14 percent, while in 2021 it will increase by 49 percent due to the transition from Conventional Banks to Sharia Banks (BSI). Then in 2022 the number of customer transactions temporarily decreased by 38 percent because it was only recorded from January to June. While the number of customer transactions in 2020 is Rp. 120,000,000, then in 2021 the number of customer transactions has increased by Rp. 600,000,000. And in 2022 temporarily decreased by Rp. 400,000,000. The method used in this article is a qualitative method, the data used is secondary data regarding the use of e-banking on customer transactions at PT. Bank Syariah Indonesia Kcp Blangpidie Kuta Tuha for the period 2020-2022. The purpose of this study was to determine the amount of use of e-banking on customer transactions at Pt. Bank Syariah Indonesia Kcp Blangpidie Kuta Tuha.